The human hippocampus and its subfield volumes across age, sex and APOE e4 status. Issue 1 (19th December 2020) - Veldsman, Michele; Nobis, Lisa; Alfaro-Almagro, Fidel; Manohar, Sanjay; Husain, Masud
Abstract: Female sex, age and carriage of the apolipoprotein E e4 allele are the greatest risk factors for sporadic Alzheimer's disease. The hippocampus has a selective vulnerability to atrophy in ageing that may be accelerated in Alzheimer's disease, including in those with increased genetic risk of the disease, years before onset. Within the hippocampal complex, subfields represent cytoarchitectonic and connectivity based divisions. Variation in global hippocampal and subfield volume associated with sex, age and apolipoprotein E e4 status has the potential to provide a sensitive biomarker of future vulnerability to Alzheimer's disease. Here, we examined non-linear age, sex and apolipoprotein E effects, and their interactions, on hippocampal and subfield volumes across several decades spanning mid-life to old age in 36 653 healthy ageing individuals. FMRIB Software Library derived estimates of total hippocampal volume and Freesurfer derived estimates hippocampal subfield volume were estimated. A model-free, sliding-window approach was implemented that does not assume a linear relationship between age and subfield volume. The annualized percentage of subfield volume change was calculated to investigate associations with age, sex and apolipoprotein E e4 homozygosity. Hippocampal volume showed a marked reduction in apolipoprotein E e4/e4 female carriers after age 65. Volume was lower in homozygous e4 individuals in specific subfields including the presubiculum, subiculum head, cornu ammonis 1 body, cornu ammonis 3 head and cornu ammonis 4. Nearby brain structures in medial temporal and subcortical regions did not show the same age, sex and apolipoprotein E interactions, suggesting selective vulnerability of the hippocampus and its subfields. The findings demonstrate that in healthy ageing, two factors—female sex and apolipoprotein E e4 status—confer selective vulnerability of specific hippocampal subfields to volume loss. Abstract : Female sex, age and carriage of the APOE e4 allele are the greatest risk factors for sporadic Alzheimer's disease. Analysis of these three risk factors on hippocampal and subfield volumes in 36 653 healthy ageing individuals show two factors—female sex and APOE e4 status—confer selective vulnerability of specific hippocampal subfields to volume loss. Graphical Abstract: